John Walworth pay order - Walworth, John.
Pay order requesting that the state of Ohio pay eight dollars to Jonathan Sealy under the provisions of an act encouraging the killing of wolves. Signed by John Walworth, Cuyahoga County.
Clerk.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Sealy, Jonathan; Gray wolf -- Ohio; Clerks